2014
DOI: 10.1111/tan.12367
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms of interleukin‐18 gene and risk of breast cancer in a Brazilian population

Abstract: Interleukin-18 (IL-18) is a key cytokine responsible for immune response and involved in the process of cancer development. In this case-control study, we tested whether IL-18 promoter polymorphism contributes to breast cancer susceptibility in Brazilian patients. The two groups studied were 154 patients with breast cancer and 118 healthy individuals. The frequency of IL-18 promoter single nucleotide polymorphisms (SNPs) at positions -607 (C/A) (rs1946518) and -137 (G/C) (rs187238) was determined by polymerase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…All association analysis was performed by SNPStats online software in which p < 0.05 is considered statistically significant (Table b and c in Supplementary material). 52 …”
Section: Discussionmentioning
confidence: 99%
“…All association analysis was performed by SNPStats online software in which p < 0.05 is considered statistically significant (Table b and c in Supplementary material). 52 …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the association of the several inflammatory or immune response-related gene polymorphisms such as CXCL12, IL-18, IL-21, IFN-γ, and TNF-α with breast cancer have been reported in different populations [24][25][26][27]. It has been reported that chemokines genetic variations may influence the susceptibility to some infectious diseases and also to a variety of noninfectious diseases such as cancer, autoimmune, and cardiovascular diseases [28].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the association was verified between the 2 SNPs and the susceptibility to many cancers, including hepatocellular carcinoma, non‐small‐cell lung cancer, papillary thyroid carcinoma, chronic leukemia, oral squamous cell carcinoma . Although there have been reports on the association analysis of the IL‐18 ‐137, and ‐607 sites with susceptibility to breast cancer, but the conclusions are not consistent …”
Section: Discussionmentioning
confidence: 93%
“…However, studies focus on the role of IL‐18 polymorphisms on the risk of breast cancer remain controversial. To the best of our knowledge, only 3 studies have estimated the impact of IL‐18 polymorphisms ‐137G/C and/or ‐607A/C on breast cancer susceptibility . Khalili et al recruited 200 breast cancer patients and 206 healthy controls to examine the effect of ‐607A/C and ‐137G/C gene polymorphism of IL‐18 on breast cancer risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation